Ungdomens poetiska form Språkets och begärets omstörtande kraft i antologierna Kärlek och uppror och Berör och förstör - Stenbeck, Evelina (Barnboken, 2021)
Siv Widerberg and Anna Artén’s poetry anthology Kärlek och uppror: 210 dikter för unga människor (Love and Rebellion: 210 Poems for Young People, 1989) is something of a classic when it comes to Swedish contemporary poetry explicitly addressing young readers. Thirty years after its publication another poetry anthology, Berör och förstör: Dikter för unga (Affect and Destroy: Poems for Youth, 2019), edited by Athena Farrokhzad and Kristofer Folkhammar, was published. Both books tap into a long tradition of lyrical anthologies. Neither of the anthologies contain poetry written primarily for young readers. On the contrary, the anthologies include poems from the Swedish lyrical canon. Although the two anthologies share a similar structure and joint themes such as youth, love, poetry, and rebellion, they are significantly different in regard to poetic form and the conceptualizations of youth. The main theoretical perspective in this study is that the form of the anthologized poems can be understood as ideological expressions of an interplay between the genre's tradition and its specific aesthetic context. By historizing the genre and comparing the different paratexts of the anthologies, the article shows that adult conceptions of youth hides behind the editorial choices. In a quest to (re)create new writing subjects, through the rebellious powers of poetic language and love, the symbolic form of youth poetry both challenges and negates adult notions of youth in the two anthologies.